Pentraxin 3, a new biomarker for the diagnosis and management of PJI in primary and revision hip arthroplasty - Logroscino, Giandomenico; Fidanza, Andrea; Giusti, Ilaria; Poppa, Giuseppina; Troianello, Luca; Calafiore, Francesco; Saracco, Michela; Avigni, Roberta; Leone, Roberto; Mantovani, Alberto; Bottazzi, Barbara; Grappiolo, Guido; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background/Aim of the study: The periprosthetic or superficial site infections are one of the most catastrophic and difficult to manage complications following total hip arthroplasty. Recently, in addition to well know systemic markers of inflammation, the blood and synovial fluid biomarkers are focused to have a possible role in the infection diagnosis. The long Pentraxin 3 (PTX3) seems to be a sensitive biomarker of acute phase inflammation. The objectives of this prospective and multicentre study were (1) to establish the plasma trend effectiveness of PTX3 in patients undergoing primary hip replacement, and (2) to evaluate the diagnostic accuracy of blood and synovial PTX3 in patients undergoing prosthetic revision of infected hip arthroplasty. Methods: Human PTX3 was measured by ELISA in two cohorts of patients, 10 patients undergoing primary hip replacement for osteoarthritis and 9 patients with infected hip arthroplasty. Results: The Authors were able to demonstrate that PTX3 is a viable biomarker for acute phase inflammation. Conclusions: An increase in PTX3 protein concentration in the synovial fluid of patients undergoing implant revision has a strong diagnostic capacity for periprosthetic joint infection, showing 97% specificity.